Pengaruh Promosi Online dan Kenyamanan Konsumen Terhadap Pembelian Produk Makanan di Toko Rumah Roti Kota Pinang Labuhanbatu Selatan - Harahap, Suryana Sinta; Ulya, Basyarul; Syafriyeti, Rahmi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the influence of online promotion and consumer convenience on the purchase of food products at the bakery house of Kota Pinang Labuhan Batu Selatan. Explanatory research method using hypothesis tests using a quantitative approach using data collection through a questionnaire. The population studied in this study is 50 active consumers at the areca nut bread house. The results of the study show that online promotion has a positive and significant effect on purchase decisions, and convenience also has a positive and significant effect on purchase decisions at the Kota Pinang Bakery. Keywords : Online Promotion, consumer convenience, Purchase Decision.